Flex 3 with Java : develop rich internet applications using Adobe Flex 3 and ActionScript 3.0, and integrate them with a Java backend using BlazeDS 3.2 /: develop rich internet applications using Adobe Flex 3 and ActionScript 3.0, and integrate them with a Java backend using BlazeDS 3.2. (2009) - Unknown
No abstract available